Research regarding the influence of different printing strategies on the mechanical characteristics of some FDM manufactured structures. Issue 1 (1st October 2022) - Besnea, D; Rizescu, C I; Spanu, A; Moraru, E; Rizescu, D; Constantin, V; Panait, I
Abstract : The aim of this paper is to present a study we already performed regarding the mechanical behaviour of different structures for infill patterns obtained by fused deposition modelling (FDM). This time, the authors used different infill factors (10%, 30% and 60%) and different printed pattern strategies (diamond, honeycomb, linear, wiggle), after which the structures obtained with the above parameters were evaluated from a mechanical point of view to identify the optimal variant, because the printing conditions play an important role, as they can particularly influence the properties of 3D printed structures that can be used, for example, as device (instrument) housing or functional tests. The experimental determinations were performed at the Laboratory of Ultra-precise Systems for Precision Mechanics from UPB to observe how printing strategies correlated with infill factors influence the mechanical characteristics of manufactured structures.